The Role of Technology-Based Education and Teacher Professional Development in English as a Foreign Language Classes - Zhang, Weihong (Frontiers in Psychology, 2022)
The swift development of technology has had a considerable effect on teaching, especially in foreign language classes and the rising procedure of using creative technology to help teachers’ instruction and learning indicates the growing domination of technology in academic environments. In addition, teacher professional development significantly affects enhancing the teaching quality, especially the quality of educational activities within the class. Nevertheless, the shortage of workshops on professional development education made educators reliant on informal education where they worked and learned collectively with classmates in mini-groups to enhance their technology usage. The functions of technology-based instruction in the process of learning have not been taken into account in the professional development programs in the Chinese context so far and consequently, this review takes a look at the issue. In a nutshell, this review of literature has suggestions for academics, theoreticians, and experts in search of inspecting the roles of technology in teacher professional development programs.